ACCOUNTABILITY OF POST-DISASTER FUND ACCOUNTABILITY REPORTING AND ITS CONTRIBUTION TO ACCELERATING DEVELOPMENT IN WEST NUSA TENGGARA PROVINCE, 2018–2022 - Hariadi KL; Handayani Lilik; Sokarina Ayudia (PT. Hasba Edukasi Mandiri, 2026)
West Nusa Tenggara (NTB) Province is a disaster-prone region that experienced severe earthquake impacts in 2018, particularly in the housing sector. The Indonesian Government allocated Ready-to-Use Funds (Dana Siap Pakai/DSP) through the National Disaster Management Agency (BNPB) to support the acceleration of post-disaster rehabilitation and reconstruction. However, implementation faced several challenges, including complex coordination among stakeholders, slow verification of aid beneficiaries, limited local government budget capacity, and the impact of the Covid-19 pandemic. This study aims to analyze the accountability of post-disaster aid accountability reporting and its contribution to development acceleration in West Nusa Tenggara Province during the 2018–2022 period. Using a qualitative case study approach, the findings indicate that accountability in aid accountability reporting plays a significant role in improving fund distribution effectiveness, accelerating decision-making, and supporting the acceleration of post-earthquake development. These findings emphasize that strengthening accountability in post-disaster aid reporting is a key factor in achieving successful post-disaster development.